2011
DOI: 10.1111/j.1538-7836.2011.04256.x
|View full text |Cite
|
Sign up to set email alerts
|

High levels of protein C are determined by PROCR haplotype 3

Abstract: Summary. Background: Genetic determinants of plasma levels of protein C (PC) are poorly understood. Recently, we identified a locus on chromosome 20 determining high PC levels in a large Dutch pedigree with unexplained thrombophilia. Candidate genes in the LOD-1 support interval included FOXA2, THBD and PROCR. Objectives: To examine these candidate genes and their influence on plasma levels of PC. Patients/Methods: Exons, promoter and 3¢UTR of the candidate genes were sequenced in 12 family members with normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
2
11
1
Order By: Relevance
“…We were able to detect associations between two tightly linked SNPs from the PROCR genomic region (coding for EPCR) and PC plasma levels, also found in previous studies [15], [16], [18], [19]. In this respect, these particular results of ours stand as an independent replication from a family-based perspective.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We were able to detect associations between two tightly linked SNPs from the PROCR genomic region (coding for EPCR) and PC plasma levels, also found in previous studies [15], [16], [18], [19]. In this respect, these particular results of ours stand as an independent replication from a family-based perspective.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, a genome-wide linkage analysis reported that a quantitative trait locus in chromosomal region 20q11 (including genes FOXA2 , THBD and PROCR ) influences PC levels in one extended family from the GENES study [17], [18]. A subsequent study revealed that PROCR haplotype 3 and a SNP from FOXA2 (rs1055080) were associated with PC levels in this family, but only PROCR haplotype 3 was associated also with plasma levels in healthy individuals [19].…”
Section: Introductionmentioning
confidence: 94%
“…One of these haplotypes, A3, encodes a protein, which is more sensitive than the other two to the action of shedding enzymes, which can result in a marked increase in the level of sEPCR. The presence of the A3 haplotype therefore coincides with the presence of a high sEPCR level, the latter being a candidate risk factor for venous thrombosis (1012). Interest in EPCR/aPC in relation to tumor biology is gaining momentum with the appearance of an increasing number of publications (1316).…”
Section: Introductionmentioning
confidence: 87%
“…Soluble EPCR is shed from endothelial cells by metalloproteinase TACE/ADAM17 and circulates in plasma 19 . The levels of soluble EPCR differ between individuals and high plasma levels of EPCR (up to 500 ng/ml) are associated with specific PROCR haplotypes 20 , which in turn are associated with a higher risk of contracting venous thrombosis 21 . Of interest, addition of recombinant soluble EPCR at levels between 15–300 ng/ml showed a progressively higher inhibition of the binding between DC8 expressing parasites and endothelial cells (Fig.…”
mentioning
confidence: 99%